Output of phylodynamic (BD) and SEIR model to estimate the effective reproduction number of between-pen transmission (between-pen Re) for farm B, compartment 2 during weeks 7 to 16 of batch B. - Marina Meester (11765542) (2025)
Legend: The solid line at week 14 indicates the implemented change time for the BD model as all pens were HEV positive in this week according to infection dynamics data. Numbers at the internal nodes represent bootstrap support values. 3A: Maximum clade credibility (MCC) tree of the BD model estimated from 9 whole genome sequences from pens in compartment 2. 3B: Between-pen Re estimates with 95% highest posterior density intervals from phylodynamic BD and mechanistic SEIR models over time.